Prevalence and genetic diversity of canine coronavirus in northeastern China during 2019–2021. (March 2023) - Li, Nuowa; Bai, Yue; Liu, Runhang; Guo, Zhiyuan; Yan, Xin; Xiang, Kongrui; Liu, Feng; Zhao, Lili; Ge, Junwei
Abstract: Canine coronavirus (CCoV) is associated with diarrhea in dogs, with a high incidence and sometimes even death. However, there is currently limited information about its prevalence and molecular characterization in northeastern China. Therefore, in this study, we examined 325 canine fecal specimens in four provinces in northeastern China from 2019 to 2021. PCR results revealed that 57 out of 325 (17.5%) samples were found to be positive for CCoV, and the positive rate varies obviously with city, season, age and so on. High incidence (65%) of viral co-infection was detected in the diarrhea samples and mixed infection of distinct CCoV genotypes occurs extensively. More importantly, sequence analysis showed that the S gene has a strong mutation. Phylogenetic analysis demonstrated that CCoV-I and CCoV-II strains has different origins. In particular, we found the CCoV-IIa strains of S gene sequenced and the reference strain B906_ZJ_2019 were highly clustered, and the reference strain was a recombinant strain of CCoV-I and CCoV-II. Our findings provide useful orienting clues for evaluating the pathogenic potential of CCoV in canines, and point out more details on characterization in northeastern China. Further work is required to determine the significance and continuous genetic evolution of CCoV. Highlights: The detection covers the whole northeastern China, with a detection rate of 17.5% (57/325). The positive rate varies significantly with city, season, age and so on. The incidence of co-infection is high, and multiple genotypes coexist in one positive sample. Virus detection should be closely monitored in dogs that have completed the immunization program. Pathogenicity needs to be reassessed.